Passive Vibrations Control of Ultrasonic Machining Subjected to Tuned and External Forces - , Yaser A. Amer; Mai M. Agwa, (IJRDO-Journal of Applied Science, 2019)
Linear passive control is used to study and description the vibration of the ultrasonic machining (USM) non-linear dynamical system is consists of tuned and external force .The system is represented by a two-degree-of-freedom (2DOF).The method of multiple scales perturbation technique (MSPT) is applied to obtain approximate solution. The vibration is studded numerically on the system with and without control .The stability at the worst resonance cases ( , , , , ) is obtained using both phase plane methods and frequency response of resonance case. Effects of different parameters on the system behavior are studied numerically by using MATLAB program. Finally, a comparison of previously published work is done.